PERAN SEKOLAH RAMAH ANAK DALAM MENINGKATKAN AKHLAK PESERTA DIDIK STUDI KASUS DI MADRASAH TSANAWIYAH NEGERI 6 JOMBANG - Ummah, Aslikhatul; Umam, Khoirul; Ilahiyah, Iva (EL-Islam, 2024)
This study discusses the role of child-friendly schools in improving the morals of students in Madrasah Tsanawiyah Negeri 6 Jombang. This type of case study research belongs to this type of research. The qualitative approach uses data retrieval techniques such as observation, interviews, and documentation, and data analysis techniques such as data reduction, presentation, and verification. The results of research conducted on the role of child-friendly schools in improving the morals of students in MTsN 6 Jombang. So there is a role for child-friendly schools in improving the morals of students so that akhlakul karimah is embedded in students. Through child-friendly school policies, several points can be taken in improving the morals of students. Such as child-friendly school policies, curriculum implementation, child-friendly school facilities and infrastructure, child participation, and participation of various elements of society. From these policies, it can improve the morals of students such as responsible, discipline, friendly to others, polite to others. There are supporting factors, namely all parties who contribute related in improving the morals of students. Such as educators, students, parents, the community, and the government. With this policy, Child Friendly School has a role in improving the morals of students.